2019
DOI: 10.1021/acscatal.9b02348
|View full text |Cite
|
Sign up to set email alerts
|

Cupraelectro-Catalyzed Alkyne Annulation: Evidence for Distinct C–H Alkynylation and Decarboxylative C–H/C–C Manifolds

Abstract: Synthetically meaningful isoindolones were accessed by cupraelectro-catalyzed C–H activation with electricity as terminal oxidant. Thus, a versatile, inexpensive, and nontoxic Cu­(OAc)2 catalyst enabled broadly applicable C–H/N–H functionalizations on electron-rich and electron-deficient benzamides with distinct functional group tolerance and resource-economy. Detailed mechanistic studies provided strong support for a C–H alkynylation mechanism through fast C–H metalation, which likewise set the stage for cupr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 88 publications
0
48
0
1
Order By: Relevance
“…Electrochemical C−H activated annulation reaction has proven as a powerful and step‐economical method to synthesize heterocycles by C−H/N−H functionalizations [58] . Recently, Ackermann et al reported the first electrochemical Cu‐catalyzed decarboxylative alkyne annulation reaction to synthesize bioactive isoindolones compounds [59] . The desired isoindolones were obtained by reaction of N ‐protected benzamide and alkynyl carboxylic acids in the presence of RVC anode and platinum cathode at a constant current of 6.0 mA in an undivided cell (Scheme 29).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical C−H activated annulation reaction has proven as a powerful and step‐economical method to synthesize heterocycles by C−H/N−H functionalizations [58] . Recently, Ackermann et al reported the first electrochemical Cu‐catalyzed decarboxylative alkyne annulation reaction to synthesize bioactive isoindolones compounds [59] . The desired isoindolones were obtained by reaction of N ‐protected benzamide and alkynyl carboxylic acids in the presence of RVC anode and platinum cathode at a constant current of 6.0 mA in an undivided cell (Scheme 29).…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…[58] Recently,A ckermann et al reported the first electro-chemicalC u-catalyzed decarboxylative alkyne annulation reaction to synthesize bioactive isoindolones compounds. [59] The desired isoindolones were obtained by reaction of N-protected benzamide and alkynyl carboxylic acids in the presence of RVC anode and platinum cathode at ac onstant current of 6.0 mA in an undivided cell (Scheme 29). This strategy features the substrate scope with different alkynylc arboxylic acids.…”
Section: Electrochemical Cu-catalyzed Càhd Ecarboxylative Alkyne Annumentioning
confidence: 99%
“…Copper salts have constituted one of the most commonly used catalysts in organic synthesis due to their low price and low toxicity. In 2019, Ackermann and co-workers [47] reported an electrocatalytic method involving copper-catalyzed annulations of benzamides with alkynes for synthesizing isoindolones. The optimized reaction conditions were obtained under a constant current of 6.0 mA in an undivided cell equipped with an RVC anode and platinum plate cathode, using 5.0 mol% of Cu(OAc) 2 •H 2 O as a redox catalyst and NaOPiv as an additive in DMF.…”
Section: Copper-catalyzed Intermolecular Annulations Of Alkynesmentioning
confidence: 99%
“…developed using catalysts including Co, 13 Ru, 14 Rh, 15 and Cu. 16 In contrast, electrochemical vinylic C-H annulation with alkynes is less studied. Recently, we reported an Ir-catalyzed electrochemical vinylic C-H annulation reaction of acrylic acids with internal alkynes, affording α-pyrones in good yields, but terminal alkynes are not tolerated.…”
Section: Scheme 1 Rh-catalyzed Vinylic C-h Annulation Of Acrylamidesmentioning
confidence: 99%